Nature-Inclusive Corporate Governance: Identifying Four Emergent Models and Analysing Outcomes - Ebba Hooft Toomey; Tineke Lambooy (Universitas Airlangga, 2026)
This paper investigates the emerging field of Nature inclusive corporate governance, which gives voice to a historically ‘silent’ stakeholder. Nature governance has the potential to break down the human nature dichotomy of organizational governance and management and offers a tool to bring organizational operations into alignment with natural systems. However, no academic research has been done on the effectiveness of Nature governance models in providing Nature with representation. Therefore, this paper conducts an exploratory study utilizing comparative, inductive, qualitative analyses of interviews with 10 case study companies to investigate 1) the outcomes of Nature governance, to test for policy-practice decoupling, and 2) the levels of satisfaction of case study companies with a governance model, to test for means-end decoupling. The discussion finds that companies have a high level of satisfaction with their model, suggesting they are fit for purpose, and report positive outcomes in the areas of culture, operations, and leadership. However, these findings serve only as a starting point for scholarly research as the case studies for this emergent phenomena are biased towards self-elected small-medium enterprises with a founding sustainability mission.